2017
DOI: 10.1002/jcad.12131
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Dynamics of Counseling Leadership: A Content Analysis Study

Abstract: The authors synthesized counseling leadership literature to identify themes of counseling leadership. Using an inductive approach to content analysis, the authors analyzed 11 empirical articles, 9 conceptual articles, and 13 leadership profiles. Results yielded 24 emergent leadership themes that were sorted into 3 groups. Findings pave the way for more comprehensive research on counseling leadership and allow for increased intentionality in teaching, training, and practicing counseling leadership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 33 publications
3
26
0
Order By: Relevance
“…Although Murphy and Johnson () began their conceptual life‐span model of leadership identity development with genetics and personalities, the data in our study pointed to relationships and context as beginning points for leadership. This is congruent with other researchers’ findings that parental influences, cultural worldviews, and early educational experiences in school, clubs, student government, and sports fostered specific values that led to leadership experiences and a sense of responsibility (McKibben et al, ; Nassar‐McMillan, ; Smith & Roysircar, ). We also found that the participants in our study described individuals and experiences that provided a foundation for their leadership identity development during sensitive periods of development (Bornstein, ).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Although Murphy and Johnson () began their conceptual life‐span model of leadership identity development with genetics and personalities, the data in our study pointed to relationships and context as beginning points for leadership. This is congruent with other researchers’ findings that parental influences, cultural worldviews, and early educational experiences in school, clubs, student government, and sports fostered specific values that led to leadership experiences and a sense of responsibility (McKibben et al, ; Nassar‐McMillan, ; Smith & Roysircar, ). We also found that the participants in our study described individuals and experiences that provided a foundation for their leadership identity development during sensitive periods of development (Bornstein, ).…”
Section: Discussionsupporting
confidence: 89%
“…When encouraged to reflect on effective leadership, core counseling listening skills emerged as those that inspired others and created trusting relationships. McKibben et al () and Yeager and Callahan () both emphasized how authenticity in leader–follower relationships is key to effective leadership. Authenticity breeds trust in relationships, so our participants may have found that developing those types of relationships reinforced their sense of self as a leader that reciprocates the effect in future leadership experiences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations